Bowel obstruction due to the migration of the deflated intragastric balloon, a rare and potentially lethal complication - Molina, Gabriel A (J Surg Case Rep, 2019)
Obesity is a worldwide epidemic that carries significant morbidity and mortality. There are many weight loss strategies available, yet to this date, none are risk-free. Intragastric balloons have been used for decades as a temporary measure for weight reduction and can be a useful approach for specific patients. Serious complications related to the device remain rare; however, prompt intervention is usually needed when they arise. We present the case of a 38-year-old female patient, she was using an intragastric balloon to treat her obesity. Regretfully, the balloon deflated causing intestinal migration and obstruction. After a successful surgery, the patient completely recovered.